"Hard, " "Soft, " or "Tough Love" Management: What Promotes Successful Performance in a Cross-Organizational Collaboration?. Issue 2 (2nd April 2016) - Kelman, Steven; Hong, Sounman
ABSTRACT: One of the most pervasive debates in literature on managing people is whether using "hard" or "soft" approaches—seeking to influence behavior by pressuring or by nurturing—produces better organizational performance. This article examines this question in the context of a cross-organizational collaboration in English local government between police, probation, social work, and other organizations designed to reduce crime. Using a survey to gather data about the organizational context of these collaborations and actual crime data, we find interaction effects between the joint presence of "hard" and "soft" features in explaining crime reduction. Taking a phrase from pop psychology, it appears that organizations characterized by "tough love" perform better than those with only "hard" or "soft" features by themselves. We suggest that further research be conducted on the relationship of "tough love" to organizational performance.